Makanatu al-Bi'h al-Ijtima'iyah Fi Ta'lim Maharah al-Kalam Laday al-Thullab Fi Ma'had Hubb al-Wathan Duri Riau - Gita Ria Farlina (Institut Agama Islam Negeri Curup, 2018)
This article discusses the social environment and its place in the teaching of speech skills among students at the Ma'had Hubb al-Wathan Duri Riau. The purpose of this research is to find out the status of the social environment at the Ma'had Hubb al-Wathan Duri Riau and its effects on the teaching of skill to speak to students at the Ma'had Hubb al-Wathan Duri Riau. The approach in this is analytical qualitative field research. The social environment around the Ma'had Hubb al-Wathan Duri Riau is a milieu environment the Malay society around the Ma'had Hubb al-Wathan Duri Riau. The ability to speak is the ability of students to good speech skills in the classroom was or outside the pronunciation of the words of the Arab and the tone and tone, and upgrade their ability, the teacher and supervisor of the Institute around the Institute, including the daily conversation in two languages and give the vocabulary and the Declaration and the operative and the lecture in three languages, but the environment around the Institute did not Supports students ability to speak Arabic and it affects students' ability to speak well. From these situations, the writer found that the social environment affects the promotion of speech skills. And the formation of the linguistic environment indicates its impact on the ability of students to upgrade the skill of speech. Keyword: social environment, education, speech skills